2015
DOI: 10.5539/ass.v11n28p139
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of High Performance Work System in Public Organizations: Implication for Organizational Performance.

Abstract: A principal concern among organizational researchers is to understand why some organizations irrespective of size and location outperform others. High performance work system (HPWS) offers an explanation for this phenomenon. HPWS gives organizations the competitive advantage over others. While it has been established that HPWS affect the performance of organizations within a large and complex organizations, less have been empirically established if it also create benefit for public organizations. This has gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Authors found that destructive organizational politics had a negative impact on knowledge-sharing and hence creativity of employees. Also Ugheoke et al (2015) investigated the relationship between three dimensions of HPWS and organizational performance and found that two out of three dimensions of HPWS were significantly associated with improved organizational performance. Similarly Fidan and Oztürk (2015) checked the relationship between Intrinsic motivation, innovative environment, and creativity and reported that intrinsic motivation was a significant predictor of the teacher creativity teachers working at private schools tend to be more intrinsically motivated and creative than teachers working at public schools.…”
Section: Fig 1 Research Frameworkmentioning
confidence: 99%
“…Authors found that destructive organizational politics had a negative impact on knowledge-sharing and hence creativity of employees. Also Ugheoke et al (2015) investigated the relationship between three dimensions of HPWS and organizational performance and found that two out of three dimensions of HPWS were significantly associated with improved organizational performance. Similarly Fidan and Oztürk (2015) checked the relationship between Intrinsic motivation, innovative environment, and creativity and reported that intrinsic motivation was a significant predictor of the teacher creativity teachers working at private schools tend to be more intrinsically motivated and creative than teachers working at public schools.…”
Section: Fig 1 Research Frameworkmentioning
confidence: 99%
“…Increased competition has pressurized organizations to train their staff with best knowledge, abilities and skills to perform competently. Researchers have given much attention to employees training and development (Aragón, Jiménez, & Valle, 2014;Ugheoke et al, 2015), because according to Ballesteros-Rodríguez, De Saá-Pérez, and Domínguez-Falcón (2012), it not only improves employee's performance but organizational performance as well.…”
Section: Training and Developmentmentioning
confidence: 99%
“…HR literature concern about HR practices that can lead to organization performance. HPWS was one of their concerns, sometimes called high-performance HR practices , which are composed of different set of practices that improve business performance (Chahal & Jyoti, 2016;Ugheoke, et al, 2015). HPWS is viewed as a system of interconnected and reinforcing HR practices including performance appraisal, selective staffing, clear job description and training.…”
Section: Theoretical Background Highperformance Work Systemsmentioning
confidence: 99%